Answer:
B) The function shown is [tex]f(x)=\frac{(x-3)(x+1)}{x}[/tex]
Step-by-step explanation:
The given function is
[tex]f(x)=\frac{x^2-2x-3}{x}[/tex]
This is an improper rational function because the degree of the numerator is greater than the degree of the denominator. This means the function has a slant asymptote and cannot have a horizontal asymptote.
The vetical asymptote is [tex]x=0[/tex].
We factor the numerator to get;
[tex]f(x)=\frac{x^2-3x+x-3}{x}[/tex]
[tex]f(x)=\frac{x(x-3)+1(x-3)}{x}[/tex]
The function shown is the same as [tex]f(x)=\frac{(x-3)(x+1)}{x}[/tex]
The zeros of this function are [tex]x=-1,x=3[/tex]
The correct answer is B